Preliminary chemical studies at the jericho archaeological site (Brazilian Journal of Radiation Sciences (BJRS), 2021)
This study measured the chemical composition of 45 ceramic samples from the Jericho archaeological site, Palestine, by means of instrumental neutron activation analysis (INAA). The mass fraction of Na, K, La, Sm, Yb, Lu, U, Sc, Cr, Fe, Co, Zn, Rb, Cs, Ce, Eu, Hf and Th was determined with the purpose to detect the presence of ceramic groupings based on their composition. The analytical method is appropriate for this type of study because it is a non-destructive technique with high sensitivity, accuracy and precision, and determines chemical elements in trace and ultra-trace levels. These characteristics are essential to study small concentration variations. Initially the mass fractions were normalized to compensate for the large difference in magnitude among elements determined in percentage and trace level. Subsequently, the dataset was interpreted through cluster and discriminant analysis. The results showed the existence of three different chemical groups.